The Response and Negotiation of Pesantren in Maintaining the Values of Pesantren During the Covid-19 Pandemic: A Case Study of Pondok Pesantren Darussunnah Hadith - Arif Zamhari; Ismi Rahmayanti (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
As a result of the Covid-19 pandemic, all aspects of education must changes and adjustments, including Islamic boarding schools (Pesantren). This educational institution must adapt the learning system by implementing various kinds of learning methods. This article was to analyze how Islamic boarding schools in urban areas respond to this pandemic by conducting a blended learning system as an alternative to teaching pesantren values and religious sciences. This study used a case study approach by conducting a series of in-depth interviews and engaging observations with strict health protocols. The result showed that the blended learning between the offline learning system for some students who live in the pesantren and online for students who live at home was less effective in teaching the values of the pesantren. This research showed that the ability of the pesantren in innovation learning and negotiate between the values of the pesantren and the conditions of the Covid-19 pandemic. The pesantren still maintains the values of the pesantren with the obstacles that arise during the teaching and learning process even though the teaching and learning process was carried out online and some students’ learning at home. Keywords: Islamic Value Pesantren, Pesantren on Covid-19, Maintaining Value Pesantren